IMPLEMENTATION OF ISLAMIC CHARACTER EDUCATION AT THE TIME OF THE PROPHET MUHAMMAD IN MADINAH - Imam Tabroni; Rini Purnama Sari (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
During the education period in Medina, it was a continuation of the struggle in Mecca, in Medina the Prophet had experienced ease in the Islamic struggle because previously the people of Medina always waited for the arrival of the Prophet Muhammad, at that time in Medina there were indeed many groups such as Aus , Khazraj , people of Muslims, Jews, Christians, but the Messenger of Allah easily united all these groups under the command of the Messenger of Allah. In various ways, it is done in order to conquer them including using the Qur'an as an educational curriculum, Aqidah as the basis for the material being taught, then using mau'izah hasanah as the method. While in Medina the mosque was very active as a central institution of Islamic education. which is no less important than the achievement of education in Medina, namely the close brotherhood between Muslims and non-Muslims.